2020
DOI: 10.1182/hematology.2020000098
|View full text |Cite
|
Sign up to set email alerts
|

Updates in infection risk and management in acute leukemia

Abstract: Patients with hematologic malignancies are at increased risk of infection, with associated morbidity and mortality. Patients with acute myeloid leukemia (AML) have qualitative and quantitative deficits in granulocytes predisposing to bacterial and fungal infections. Acute lymphoblastic leukemia results in qualitative deficits in lymphocytes, resulting in hypogammaglobulinemia and reduced cell-mediated immunity predisposing to certain bacterial and viral as well as fungal infections. Chemotherapeutic regimens o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…In addition, China is a major hepatitis country, and one-tenth of population is a carrier of HBV. At the same time, whether family history of tumors is a risk factor for predicting the onset of AML is also a controversial issue ( 33 ). For children, in addition to the above factors, they will also be affected by maternal factors related to pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, China is a major hepatitis country, and one-tenth of population is a carrier of HBV. At the same time, whether family history of tumors is a risk factor for predicting the onset of AML is also a controversial issue ( 33 ). For children, in addition to the above factors, they will also be affected by maternal factors related to pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Only two older trials [ 78 , 81 ] within the meta-analysis by Yahav et al [ 33 ] reported about patients with acute lymphoblastic leukaemia. As these patients are exposed to even more intensive and prolonged chemotherapy protocols, including corticosteroids and sometimes anti-CD20 monoclonal antibodies (see below “Patients with lymphoma”) [ 84 ], antiviral prophylaxis to reduce reactivation of HSV and VZV is recommended for patients with acute lymphoblastic leukaemia while on treatment (BI) (Table 6 ).…”
Section: Patient Groupsmentioning
confidence: 99%
“…Common treatment toxicities such as nausea, constipation or diarrhea should be prevented or rapidly treated. Anti-infective prophylaxis should be individualized depending on neutrophil count, anti-leukemic drug administered and patients' comorbidities [249].…”
Section: Supportive Carementioning
confidence: 99%